A rubber toughened polyvinyl chloride composite and a method for preparing the same

CN122917461APending Publication Date: 2026-10-16SHANDONG OU SHENG CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611234845.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]本发明的目的在于提供一种橡胶增韧聚氯乙烯复合材料组合物,以解决单一全硫化粉末丁腈橡胶界面应力传递不足,以及单一未交联或低交联丁腈橡胶容易发生流动、聚并并导致聚氯乙烯刚度和耐热性能下降的问题

Benefits of technology

1.本发明通过加入全硫化粉末丁腈橡胶,能够提高聚氯乙烯材料的冲击能量吸收能力;通过加入适量羧基丁腈橡胶,有利于改善交联橡胶粒子与聚氯乙烯基体之间的应力传递,并提高全硫化粉末丁腈橡胶的有效增韧效率;通过加入特定比例的镁铝水滑石,可以对羧基丁腈橡胶的运动状态进行调节,降低羧基丁腈橡胶在加工过程中发生过度流动或聚并的倾向,并对因橡胶加入造成的刚度和耐热性能下降进行一定程度的补偿。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application belongs to the technical field of polymer material modification, and discloses a rubber toughened polyvinyl chloride composite material and a preparation method thereof. The material comprises 6-16 parts of full-vulcanized powder nitrile rubber, 1.5-5 parts of carboxyl nitrile rubber, 0.8-4.5 parts of magnesium-aluminum hydrotalcite, 2-6 parts of a thermal stabilizer, 0.5-3 parts of a processing aid, and 0.2-2 parts of a lubricant. The full-vulcanized powder nitrile rubber forms a stable particle toughening phase, the carboxyl nitrile rubber is used for adjusting the interfacial stress transfer, and the magnesium-aluminum hydrotalcite is used for adjusting the motion state of the carboxyl nitrile rubber and has the functions of rigidity compensation and thermal stabilization. The composition can improve the impact performance of the polyvinyl chloride while reducing the adverse effects of rubber toughening on rigidity, heat resistance and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer material modification technology, specifically relating to a rubber-toughened polyvinyl chloride composite material and its preparation method. Background Technology

[0002] Polyvinyl chloride (PVC) possesses good chemical resistance, flame retardancy, dimensional stability, and processing adaptability, making it widely used in construction, piping, electrical appliances, transportation, and general industrial products. However, unplasticized or low-plasticized PVC materials typically suffer from high notch sensitivity, insufficient low-temperature toughness, and susceptibility to brittle fracture upon impact.

[0003] To improve the impact resistance of polyvinyl chloride (PVC) materials, existing technologies typically incorporate chlorinated polyethylene, methyl methacrylate-butadiene-styrene copolymer, acrylate core-shell toughening agents, nitrile rubber, or other elastomers into PVC. The rubber phase can form a flexible dispersed phase within the PVC matrix, inducing energy-dissipating processes such as shear yielding, crazing, interfacial debonding, or cavitation upon impact, thereby improving the material's impact performance. However, current rubber toughening techniques suffer from the following problems: Firstly, when using ordinary uncrosslinked rubber to toughen PVC, the rubber phase may deform, coalesce, or become locally continuous during the melt mixing process. As the amount of rubber increases, although the material may achieve higher impact performance, its tensile strength, flexural modulus, Vicat softening temperature, and dimensional stability often decrease significantly, and processing torque, discharge stability, and batch repeatability may be affected.

[0004] Secondly, when using fully vulcanized powdered nitrile rubber, its rubber particles can maintain a relatively good particulate state during the melt processing of polyvinyl chloride, serving as a stable impact-absorbing phase. However, when using only fully vulcanized powdered nitrile rubber, the interfacial bonding and stress transfer capacity between the crosslinked rubber particles and the polyvinyl chloride matrix may still be insufficient; inadequate dispersion of rubber particles may also lead to problems such as low toughening efficiency, fluctuations in impact performance, or high rubber dosage.

[0005] Third, when using carboxylated nitrile rubber, both it and polyvinyl chloride (PVC) have a certain degree of polarity, which can be used to adjust the interaction between the rubber phase and PVC. However, carboxylated nitrile rubber itself is a flexible rubber phase that can flow or deform. If its addition is too high, it may reduce the stiffness and heat resistance of PVC materials, and may cause excessive flow or aggregation during the mixing process.

[0006] Therefore, there is a need to provide a polyvinyl chloride material composition that can improve the impact performance of polyvinyl chloride while minimizing the adverse effects of rubber toughening on the material's stiffness, heat resistance, thermal stability, and processing performance. Summary of the Invention

[0007] The purpose of this invention is to provide a rubber-toughened polyvinyl chloride composite material composition to solve the problems of insufficient interfacial stress transfer of single fully vulcanized powder nitrile rubber, and the easy flow and aggregation of single uncrosslinked or low-crosslinked nitrile rubber, which leads to a decrease in the stiffness and heat resistance of polyvinyl chloride.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: To achieve the above objectives, the present invention provides a rubber-toughened polyvinyl chloride composite material composition, comprising, by weight: 100 parts of polyvinyl chloride resin, 6-16 parts of fully vulcanized powdered nitrile rubber, 1.5-5 parts of carboxylated nitrile rubber, 0.8-4.5 parts of magnesium aluminum hydrotalcite, 2-6 parts of heat stabilizer, 0.5-3 parts of processing aid, and 0.2-2 parts of lubricant.

[0009] Preferably, the mass ratio of fully vulcanized powdered nitrile rubber to carboxylated nitrile rubber is 3:1 to 6:1.

[0010] More preferably, the mass ratio of fully vulcanized powdered nitrile rubber to carboxylated nitrile rubber is 3.8:1 to 4.5:1.

[0011] Preferably, the mass ratio of magnesium aluminum hydrotalcite to carboxylated nitrile rubber is 0.4:1 to 1.2:1.

[0012] More preferably, the mass ratio of magnesium aluminum hydrotalcite to carboxylated nitrile rubber is 0.6:1 to 0.8:1.

[0013] Preferably, the total amount of fully vulcanized powdered nitrile rubber and carboxylated nitrile rubber is 8 to 18 parts.

[0014] More preferably, the total amount of fully vulcanized powdered nitrile rubber and carboxylated nitrile rubber is 10 to 15 parts.

[0015] The above ratio makes fully vulcanized powdered nitrile rubber the main toughening phase, carboxylated nitrile rubber the auxiliary flexible phase containing carboxyl groups, and magnesium aluminum hydrotalcite the regulating component for the motion state of carboxylated nitrile rubber, while taking into account both thermal stability and stiffness compensation.

[0016] Preferably, the polyvinyl chloride resin is a homopolymer of vinyl chloride, or a copolymer resin with vinyl chloride structural units as the main structural units.

[0017] Preferably, the polyvinyl chloride resin is a suspension polyvinyl chloride resin.

[0018] More preferably, the K value of the polyvinyl chloride resin is 60 to 68.

[0019] Preferably, the average degree of polymerization of the polyvinyl chloride resin is 850 to 1100.

[0020] Preferably, the gel content of the fully vulcanized powdered nitrile rubber is not less than 90 wt%.

[0021] Preferably, the D50 of the primary rubber particles in the fully vulcanized powdered nitrile rubber is 0.1–0.6 μm.

[0022] Preferably, the acrylonitrile structural unit content in the fully vulcanized powdered nitrile rubber is 25-36 wt%.

[0023] Fully vulcanized powdered nitrile butadiene rubber is in a rubbery state at the target service temperature of the polyvinyl chloride (PVC) material composition. Fully vulcanized powdered nitrile butadiene rubber is primarily used to form a granular rubber phase that is not easily fully leveled or continuous during melt mixing, thereby providing a stable, flexible energy-dissipating unit when the material is subjected to impact.

[0024] Preferably, the carboxylated nitrile rubber is uncured carboxylated nitrile rubber or low-gel carboxylated nitrile rubber.

[0025] Preferably, the gel content of carboxylated nitrile rubber is lower than that of fully vulcanized powdered nitrile rubber.

[0026] More preferably, the gel content of the carboxylated nitrile rubber is not higher than 30 wt%.

[0027] Preferably, the carboxyl content in the carboxylated acrylonitrile rubber is 1-3 wt%.

[0028] Preferably, the acrylonitrile structural unit content in the carboxylated nitrile rubber is 25-36 wt%.

[0029] Carboxylated nitrile rubber is used to improve stress transfer between fully vulcanized powdered nitrile rubber and polyvinyl chloride (PVC) and to create a flexible transition between rubber particles or between rubber particles and PVC.

[0030] Preferably, the molar ratio of magnesium to aluminum in the magnesium-aluminum hydrotalcite is 2.5:1 to 3.5:1.

[0031] Preferably, the D50 of the magnesium aluminum hydrotalcite is 0.3 to 1.2 μm.

[0032] Preferably, the water content of the magnesium aluminum hydrotalcite is not higher than 0.8 wt%.

[0033] Preferably, the magnesium aluminum hydrotalcite is magnesium aluminum hydrotalcite without organic surface coating treatment, or magnesium aluminum hydrotalcite with only a low degree of organic surface coating treatment.

[0034] Preferably, the surface organic matter content of the magnesium aluminum hydrotalcite is not higher than 1.5 wt%.

[0035] The surface organic matter content can be determined by thermogravimetric analysis, loss on ignition combined with blank hydrotalcite correction, or other methods that can distinguish between inorganic components and organic coatings.

[0036] Magnesium aluminum hydrotalcite retains surface metal sites or hydroxyl sites that can interact ionicly with carboxyl groups in carboxylated nitrile rubber, and retains the ability to absorb acidic substances produced during the thermal decomposition of polyvinyl chloride.

[0037] The acid neutralizing ability of magnesium aluminum hydrotalcite can be characterized using a standardized acid-base titration method. When comparing different embodiments and comparative examples, the same sample mass, acid concentration, titration endpoint, temperature, and time conditions should be used.

[0038] Preferably, the heat stabilizer is one or more of calcium-zinc composite stabilizers, organotin stabilizers, barium-zinc stabilizers, and organic auxiliary stabilizers.

[0039] More preferably, the heat stabilizer is a calcium-zinc composite stabilizer.

[0040] Preferably, the amount of heat stabilizer used is 3 to 4.5 parts.

[0041] Preferably, the processing aid is one or more of acrylate processing aids, styrene processing aids, and acrylonitrile-styrene processing aids.

[0042] More preferably, the processing aid is a high molecular weight acrylate processing aid for polyvinyl chloride processing.

[0043] The acrylate processing aids referred to in this invention are conventional polyvinyl chloride processing aids, not low-molecular-weight carboxylic acid type interface modifiers used to compete with magnesium aluminum hydrotalcite for adsorption.

[0044] Preferably, the amount of processing aid is 1 to 2 parts.

[0045] Preferably, the lubricant is one or more of polyethylene wax, oxidized polyethylene wax, paraffin wax, fatty acid ester, fatty alcohol, and metal soap.

[0046] Preferably, the total amount of lubricant used is 0.6 to 1.2 parts.

[0047] Preferably, the polyvinyl chloride material composition may further include inorganic fillers, pigments, antioxidants, ultraviolet absorbers, light stabilizers, flame retardant synergists, antistatic agents, release agents, or other additives permitted for use in the processing of polyvinyl chloride.

[0048] Preferably, the inorganic filler is selected from one or more of calcium carbonate, talc, wollastonite, and kaolin.

[0049] Preferably, the total amount of inorganic filler is 0 to 12 parts.

[0050] As a preferred embodiment, based on 100 parts of polyvinyl chloride resin, the polyvinyl chloride material comprises: 100 parts polyvinyl chloride resin, 8-13 parts fully vulcanized powdered nitrile rubber, 2-3.5 parts carboxylated nitrile rubber, 1.2-2.8 parts magnesium aluminum hydrotalcite, 3-4.5 parts calcium zinc composite stabilizer, 1-2 parts acrylate processing aids, and 0.5-1.2 parts lubricant.

[0051] As a more preferred embodiment, based on 100 parts of polyvinyl chloride resin, the polyvinyl chloride material composition includes: 100 parts of polyvinyl chloride resin, 10.5 parts of fully vulcanized powdered nitrile rubber, 2.7 parts of carboxylated nitrile rubber, 2 parts of magnesium aluminum hydrotalcite, 1.5 parts of acrylate processing aids, and 0.8 parts of lubricant.

[0052] On the other hand, the present invention also provides a method for preparing the above-mentioned polyvinyl chloride material composition, comprising the following steps: S1. Raw material preparation: Weigh out the following according to the formula: polyvinyl chloride resin, fully vulcanized powdered nitrile rubber, carboxylated nitrile rubber, magnesium aluminum hydrotalcite, heat stabilizer, processing aid, and lubricant.

[0053] S2, Magnesium Aluminum Hydrotalcite Pretreatment: The magnesium aluminum hydrotalcite is dried to reduce the amount of free and adsorbed water in it.

[0054] Preparation of S3, carboxylated butadiene-nitrile rubber-magnesium aluminum hydrotalcite predispersant: Carboxylated nitrile rubber and at least a portion of magnesium aluminum hydrotalcite are premixed to disperse the magnesium aluminum hydrotalcite in the carboxylated nitrile rubber, thereby obtaining a carboxylated nitrile rubber-magnesium aluminum hydrotalcite predispersant.

[0055] S4. Mixing of the composition: A mixture is obtained by mixing polyvinyl chloride resin, fully vulcanized powdered nitrile rubber, carboxylated nitrile rubber-magnesium aluminum hydrotalcite predispersant, heat stabilizer, processing aid and lubricant.

[0056] S5, Melt mixing: The mixture is melt-blended at a temperature at which polyvinyl chloride can be plasticized without significant thermal decomposition to obtain a rubber-toughened polyvinyl chloride composite composition.

[0057] S6. Molding: The PVC material composition after melt mixing is granulated, or directly extruded, calendered, molded, or injection molded.

[0058] Preferably, in S2, the drying temperature is 70–110°C.

[0059] More preferably, in S2, the drying temperature is 80–100°C.

[0060] Preferably, in S2, the drying time is 1 to 5 hours.

[0061] More preferably, in S2, the drying time is 1.5 to 3 hours.

[0062] Preferably, the moisture content of the dried magnesium aluminum hydrotalcite is not higher than 0.8 wt%.

[0063] Preferably, in step S3, a mixing mill, open mill, continuous mixer, or screw mixer is used.

[0064] Preferably, in S3, the mixing temperature is 70–120°C.

[0065] More preferably, in S3, the mixing temperature is 80–110°C.

[0066] Preferably, in step S3, the mixing time is 1 to 8 minutes.

[0067] More preferably, in S3, the mixing time is 2 to 6 minutes.

[0068] Preferably, in S3, the discharge temperature of the carboxylated nitrile rubber-magnesium aluminum hydrotalcite predispersant is 95-120°C.

[0069] The purpose of S3 is primarily to ensure sufficient contact and dispersion between the magnesium aluminum hydrotalcite and the carboxylated nitrile rubber, rather than to cause the carboxylated nitrile rubber to form a highly cross-linked, hardened, or difficult-to-redisperse network structure.

[0070] Preferably, in step S4, the polyvinyl chloride resin, heat stabilizer, processing aid, and at least a portion of the lubricant are first added to a high-speed mixer for a first-stage mixing.

[0071] Then, fully vulcanized powdered nitrile rubber and carboxylated nitrile rubber-magnesium aluminum hydrotalcite pre-dispersion were added, and mixing continued.

[0072] Preferably, the first stage of mixing is carried out until the material temperature reaches 80-95°C.

[0073] Preferably, the material is mixed until the temperature reaches 105-115°C before being discharged into a cold mixing device.

[0074] Preferably, in S5, a twin-screw extruder, a conical twin-screw extruder, a parallel twin-screw extruder, a mixer combined with a single-screw extruder or an open mill is used for melt mixing.

[0075] Preferably, the melt mixing temperature is 155–180°C.

[0076] Preferably, the average residence time of the material in the melt-blending equipment is 1 to 3 minutes.

[0077] Preferably, the extruder screw speed is 60–140 r / min.

[0078] The melt mixing process should fully plasticize the polyvinyl chloride and uniformly disperse the rubber components, while avoiding prolonged exposure of the material to high temperatures that could lead to significant thermal decomposition.

[0079] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention improves the impact energy absorption capacity of polyvinyl chloride (PVC) materials by adding fully vulcanized powdered nitrile rubber; by adding an appropriate amount of carboxylated nitrile rubber, it helps to improve the stress transmission between cross-linked rubber particles and PVC matrix, and improves the effective toughening efficiency of fully vulcanized powdered nitrile rubber; by adding a specific proportion of magnesium aluminum hydrotalcite, the motion state of carboxylated nitrile rubber can be adjusted, reducing the tendency of carboxylated nitrile rubber to excessive flow or agglomeration during processing, and compensating to a certain extent for the decrease in stiffness and heat resistance caused by the addition of rubber.

[0080] 2. The magnesium-aluminum hydrotalcite used in this invention can also help absorb acidic substances generated during the thermal processing or thermal aging of polyvinyl chloride, thereby improving or maintaining the thermal stability of polyvinyl chloride materials.

[0081] 3. By simultaneously limiting the mass ratio of fully vulcanized powdered nitrile rubber to carboxylated nitrile rubber, and the mass ratio of magnesium aluminum hydrotalcite to carboxylated nitrile rubber, the present invention can achieve a better balance between the energy dissipation capacity of the rubber phase, the fluidity of the rubber phase, the interfacial stress transmission, the material stiffness and thermal stability. Detailed Implementation

[0082] To enable those skilled in the art to better understand the present application, the technical solutions in specific embodiments of the present application will be clearly and completely described below. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by those skilled in the art.

[0083] Unless otherwise stated, the amounts of each component in the examples and comparative examples are expressed in parts, based on 100 parts of polyvinyl chloride resin. The materials used in this invention are: Polyvinyl chloride resin, K value 67, average degree of polymerization 1000.

[0084] Fully vulcanized powdered nitrile rubber with a gel content of 96.5 wt%, a primary particle D50 of 0.32 μm, and an acrylonitrile content of 33 wt%.

[0085] Carboxylated acrylonitrile butadiene rubber, with a carboxyl content of 2.1 wt%, an acrylonitrile content of 31 wt%, and a gel content of 8.5 wt%.

[0086] Magnesium aluminum hydrotalcite without organic surface treatment has a Mg / Al molar ratio of 3.0:1, a D50 of 0.68 μm, a water content of 0.35% by mass, and a surface organic matter content of less than 0.2 wt%.

[0087] The lightly surface-treated magnesium aluminum hydrotalcite has a Mg / Al molar ratio of 3.0:1, a D50 of 0.72 μm, a water content of 0.38% by mass, and a surface organic matter content of 1.1 wt%.

[0088] The highly hydrophobic surface-treated magnesium aluminum hydrotalcite has a Mg / Al molar ratio of 3.0:1, a D50 of 0.75 μm, a water content of 0.25 wt%, and a surface organic matter content of 5.2 wt%.

[0089] The calcium-zinc composite stabilizer mainly contains calcium stearate, zinc stearate, polyols, and β-diketone auxiliary stabilizing components.

[0090] Processing aids are acrylate processing aids used for processing polyvinyl chloride.

[0091] The lubricant consists of an internal fatty acid ester and an external polyethylene wax, with a mass ratio of 3:2.

[0092] The predispersant of carboxylated nitrile rubber (NBR) and magnesium aluminum hydrotalcite (MLT) was prepared using the following steps: Magnesium aluminum hydrotalcite was placed in a forced-air drying oven and dried at 90°C for 2 hours. After drying, it was removed and sealed for cooling. The initial temperature of the internal mixer was set to 90°C, and the rotor speed was set to 60 r / min. Carboxylated nitrile rubber was added first, and after mixing for 1 minute, magnesium aluminum hydrotalcite was added, and mixing continued for 3–5 minutes. When the mixing torque stabilized and the discharge temperature reached 105–115°C, the material was discharged, cooled, and cut into granules or crushed into particles suitable for subsequent mixing to obtain the predispersant of carboxylated nitrile rubber (NBR) and magnesium aluminum hydrotalcite.

[0093] The polyvinyl chloride (PVC) composition is prepared using the following steps: PVC resin, calcium-zinc composite stabilizer, acrylate processing aids, and lubricant are added to a high-speed mixer and mixed. When the material temperature reaches approximately 90°C, fully vulcanized powdered nitrile butadiene rubber and carboxylated nitrile butadiene rubber-magnesium aluminum hydrotalcite pre-dispersion are added, and mixing continues until the material temperature reaches approximately 110°C. The material is then discharged into a cold mixer and cooled to no higher than 45°C before being discharged to obtain a dry PVC mixture.

[0094] The dry polyvinyl chloride (PVC) compound was added to a twin-screw extruder for melt mixing and granulation. The temperature zones were set sequentially as follows: 150℃, 158℃, 165℃, 172℃, 175℃, and 170℃. The screw speed was set to 90 r / min, which could be adjusted according to the extruder specifications and torque. After cooling and pelletizing, the extrudate was left at room temperature for at least 24 hours before sample preparation.

[0095] Test specimens should be prepared using compression molding, injection molding, or extrusion followed by machining. All examples and comparative examples should use the same specimen preparation method.

[0096] When using the molding method, preheating and hot pressing are performed at 170-180℃. The hot pressing time is set to 3-8 minutes according to the thickness of the sample, and then cooled to no higher than 50℃ under pressure.

[0097] When using injection molding, the same or comparable barrel temperature, mold temperature, injection speed, holding pressure, and cooling time should be used for each embodiment and comparative example.

[0098] Example 1 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material. The raw materials are weighed according to the following parts by weight: 100 parts of polyvinyl chloride resin, 4 parts of calcium-zinc composite stabilizer, 1.5 parts of acrylate processing aid, 0.8 parts of lubricant, 8.0 parts of fully vulcanized powder, 2.0 parts of carboxylated nitrile rubber, and 1.20 parts of magnesium aluminum hydrotalcite.

[0099] Magnesium aluminum hydrotalcite was dried at 90°C for 2 hours. Carboxylated nitrile rubber and magnesium aluminum hydrotalcite were premixed in an internal mixer at 90–110°C for 4 minutes to obtain a pre-dispersion. Polyvinyl chloride resin, calcium-zinc composite stabilizer, processing aids, and lubricants were added to a high-speed mixer and mixed. When the material reached 90°C, fully vulcanized powdered nitrile rubber and the above pre-dispersion were added, and mixing continued until 110°C, followed by cooling. The resulting dry mix was subjected to twin-screw melt mixing and granulation to obtain the polyvinyl chloride material composition of Example 1.

[0100] Example 2 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material. The difference from Example 1 is that the amount of fully vulcanized powdered nitrile rubber is 10.5 parts, the amount of carboxylated nitrile rubber is 2.7 parts, and the amount of magnesium aluminum hydrotalcite is 2 parts. The remaining raw materials and preparation methods are the same as in Example 1.

[0101] Example 3 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material. The difference from Example 1 is that the amount of fully vulcanized powdered nitrile rubber is 13 parts, the amount of carboxylated nitrile rubber is 3 parts, and the amount of magnesium aluminum hydrotalcite is 2.1 parts. The remaining raw materials and preparation methods are the same as in Example 1.

[0102] Example 4 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material. The difference from Example 1 is that the amount of magnesium aluminum hydrotalcite is 1.5 parts, while the other raw materials and preparation methods are the same as in Example 1.

[0103] Example 5 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material. The difference from Example 1 is that the amount of magnesium aluminum hydrotalcite is 2.43 parts, while the other raw materials and preparation methods are the same as in Example 1.

[0104] Example 6 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material, weighing each raw material according to the formulation of Example 2. No pre-prepared carboxylated nitrile rubber-magnesium aluminum hydrotalcite pre-dispersion is used. First, the polyvinyl chloride resin, calcium-zinc composite stabilizer, processing aid, and lubricant are mixed. When the material temperature reaches 90°C, fully vulcanized powdered nitrile rubber, carboxylated nitrile rubber, and magnesium aluminum hydrotalcite are simultaneously added, and mixing continues until the temperature reaches 110°C. Subsequently, cold mixing, melt mixing, and granulation are performed according to the conditions of Example 2.

[0105] Example 7 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material. A lightly surface-treated magnesium aluminum hydrotalcite is used instead of the untreated magnesium aluminum hydrotalcite in Example 2. The remaining raw materials and preparation methods are the same as in Example 2.

[0106] Example 8 This embodiment provides a method for preparing a rubber-toughened polyvinyl chloride composite material. Based on the formulation of Example 2, 10 parts of calcium carbonate are added in addition, and the remaining raw materials and preparation methods are the same as in Example 2.

[0107] Comparative Example 1 This comparative example is the preparation without the addition of fully vulcanized powdered nitrile rubber, carboxylated nitrile rubber, and magnesium aluminum hydrotalcite. The remaining raw materials and preparation methods are the same as in Example 2.

[0108] Comparative Example 2 This comparative example is prepared by adding only 13.2 parts of fully vulcanized powdered nitrile rubber, without adding carboxylated nitrile rubber and magnesium aluminum hydrotalcite. The remaining raw materials and preparation methods are the same as in Example 2.

[0109] Comparative Example 3 This comparative example is prepared by adding only 13.2 parts of carboxylated nitrile rubber, without adding fully vulcanized powdered nitrile rubber and magnesium aluminum hydrotalcite. The remaining raw materials and preparation methods are the same as in Example 2.

[0110] Comparative Example 4 This comparative example was prepared by adding 10.5 parts of fully vulcanized powdered nitrile rubber and 2.7 parts of carboxylated nitrile rubber, without adding magnesium aluminum hydrotalcite. The remaining raw materials and preparation methods were the same as in Example 2.

[0111] Comparative Example 5 This comparative example is prepared by adding 13.2 parts of fully vulcanized powdered nitrile rubber and 2 parts of magnesium aluminum hydrotalcite, without adding carboxyl nitrile rubber. The remaining raw materials and preparation methods are the same as in Example 2.

[0112] Comparative Example 6 This comparative example uses calcium carbonate instead of the magnesium aluminum hydrotalcite in Example 2. The remaining raw materials and preparation methods are the same as in Example 2.

[0113] Comparative Example 7 This comparative example uses a magnesium aluminum hydrotalcite with a highly hydrophobic surface treatment instead of the magnesium aluminum hydrotalcite in Example 2. The remaining raw materials and preparation methods are the same as in Example 2.

[0114] Comparative Example 8 This comparative example demonstrates the preparation of a product with an excessively low amount of magnesium aluminum hydrotalcite. The amount of magnesium aluminum hydrotalcite was 0.54 parts, and the remaining raw materials and preparation methods were the same as in Example 2.

[0115] Comparative Example 9 This comparative example illustrates the preparation of an excessively high amount of magnesium aluminum hydrotalcite, with 3.51 parts of magnesium aluminum hydrotalcite used. The remaining raw materials and preparation methods are the same as in Example 2.

[0116] Test case The test items and test methods used in this test case are as follows: The notched impact performance was tested at room temperature, and the notched impact strength of the simply supported beams in each embodiment and comparative example was tested at 23°C according to the method specified in GB / T 1043.1.

[0117] For low-temperature notched impact performance testing, the sample is conditioned at -10℃ for no less than 4 hours, and the notched impact test of a simply supported beam is completed within the specified time.

[0118] Tensile properties were tested according to the method specified in GB / T 1040.2, which determined the tensile yield strength, tensile strength, and elongation at break.

[0119] Bending performance testing shall be conducted in accordance with the method specified in GB / T 9341 to determine bending strength and bending modulus.

[0120] The Vicat softening temperature test was conducted according to the method specified in GB / T 1633. All samples were subjected to the same load and heating rate.

[0121] Test Example 6 Thermal stability testing was conducted according to the method specified in GB / T 2917.1, testing the time required for the material to release acidic products at a specified temperature. The Congo red method was used, and the test temperature was 190℃.

[0122] The impact retention rate test after thermal aging involves aging the impact sample at 80°C for 168 hours, then acclimating it to a standard environment for 24 hours before testing the notched impact strength.

[0123] The test results are shown in Tables 1 and 2.

[0124] Table 1: Summary of Mechanical and Heat Resistance Test Results

[0125] The results showed that the notched impact strength at 23°C of Example 2 was increased by 27.1%, 18.1%, and 20.0% compared to Comparative Examples 2, 4, and 5, respectively, and the notched impact strength at -10°C was increased by 31.1%, 15.9%, and 23.1%, respectively. This indicates that fully vulcanized powdered nitrile rubber can provide a stable particulate energy-dissipating phase, and that carboxylated nitrile rubber and hydrotalcite together improve interfacial force transfer. The tensile yield strength of Example 2 was 97.8% of that of Comparative Example 2, and the flexural modulus was the same as that of Comparative Example 2, but increased by 9.2% compared to Comparative Example 4; the Vicat softening temperature was increased by 2.7°C compared to Comparative Example 4. This indicates that hydrotalcite can suppress excessive flow of the flexible rubber phase and reduce the loss of stiffness and heat resistance due to toughening. Under the same rubber formulation, Examples 1, 4, and 5 showed that a moderate amount of hydrotalcite provided a better impact-stiffness balance. When the dosage of Comparative Example 8 was too low, the overall improvement was insufficient. While the modulus and thermal stability time increased when the dosage of Comparative Example 9 was too high, the impact strength at 23°C and -10°C decreased significantly. The impact strength at 23°C in Example 2 was 9.5% higher than that of Example 6 without pre-dispersion. Example 7, with its light surface treatment, maintained good performance, while the impact strength and thermal stability time of the highly hydrophobic Comparative Example 7 both decreased, indicating that retaining the surface interaction sites of the hydrotalcite is beneficial for forming effective interfacial interactions. In Comparative Example 6, after replacing the hydrotalcite with an equal amount of calcium carbonate, the flexural modulus was comparable to that of Example 2, but the impact strength and thermal stability time decreased to 12.4 kJ / m². 2 And 31.0 min. Example 8 further shows that increasing calcium carbonate can improve the modulus, but sacrifices impact performance, so the hydrotalcite does not only act as a rigid filler.

[0126] Table 2: Summary of Thermal Stability and Thermal Aging Performance Test Results

[0127] The results show that the thermal stability time of Example 2 was extended by 20.6% and 16.9% compared with Comparative Example 4 and Comparative Example 2, respectively, and the impact retention rate was increased by 13 and 7 percentage points, respectively. The overall results indicate that this formulation achieves a good balance between room temperature toughness, low temperature toughness, stiffness, heat resistance, and thermal stability.

[0128] Finally, it should be noted that the described embodiments are merely some, not all, of the embodiments of the present invention. Those skilled in the art will understand that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the claims and their equivalents; that is, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A rubber-toughened polyvinyl chloride composite material, characterized in that, By weight, it includes: 100 parts polyvinyl chloride resin, 6-16 parts fully vulcanized powdered nitrile rubber, 1.5-5 parts carboxylated nitrile rubber, 0.8-4.5 parts magnesium aluminum hydrotalcite, 2-6 parts heat stabilizer, 0.5-3 parts processing aid, and 0.2-2 parts lubricant, wherein the mass ratio of fully vulcanized powdered nitrile rubber to carboxylated nitrile rubber is 3:1-6:1, and the mass ratio of magnesium aluminum hydrotalcite to carboxylated nitrile rubber is 0.4:1-1.2:

1.

2. The material according to claim 1, characterized in that, The mass ratio of fully vulcanized powdered nitrile butadiene rubber to carboxylated nitrile butadiene rubber is 3.8:1 to 4.5:

1.

3. The material according to claim 1, characterized in that, The mass ratio of magnesium aluminum hydrotalcite to carboxylated nitrile rubber is 0.6:1 to 0.8:

1.

4. The material according to claim 1, characterized in that, In fully vulcanized powdered nitrile rubber, the gel content is not less than 90 wt%, and the acrylonitrile structural unit content is 25-36 wt%.

5. The material according to claim 1, characterized in that, In carboxylated nitrile rubber, the gel content is no more than 30 wt%; the carboxyl content is 1-3 wt%; and the acrylonitrile structural unit content is 25-36 wt%.

6. The material according to claim 1, characterized in that, In magnesium aluminum hydrotalcite, the molar ratio of magnesium to aluminum is 2.5:1 to 3.5:1; the surface organic matter content is not higher than 1.5 wt%; and the water content is not higher than 0.8 wt%.

7. The material according to claim 1, characterized in that, The heat stabilizer is one or more of the following: calcium-zinc composite stabilizer, organotin stabilizer, and barium-zinc stabilizer.

8. The material according to claim 1, characterized in that, The processing aid is one or more of the following: acrylate processing aids, styrene processing aids, and acrylonitrile-styrene processing aids.

9. A method for preparing the rubber-toughened polyvinyl chloride composite material according to any one of claims 1-8, characterized in that, Includes the following steps: S1. Weigh out the following according to the formula: polyvinyl chloride resin, fully vulcanized powdered nitrile rubber, carboxylated nitrile rubber, magnesium aluminum hydrotalcite, heat stabilizer, processing aid and lubricant. S2. Dry the magnesium aluminum hydrotalcite to reduce the free water and adsorbed water in the magnesium aluminum hydrotalcite. S3. Premix carboxylated nitrile rubber and at least a portion of magnesium aluminum hydrotalcite to disperse the magnesium aluminum hydrotalcite in the carboxylated nitrile rubber, thereby obtaining a carboxylated nitrile rubber-magnesium aluminum hydrotalcite predisperse. S4. Mix polyvinyl chloride resin, fully vulcanized powdered nitrile rubber, carboxylated nitrile rubber-magnesium aluminum hydrotalcite predispersant, heat stabilizer, processing aid and lubricant to obtain a mixture; S5. The mixture is melt-blended to obtain a rubber-toughened polyvinyl chloride composite material.

10. The preparation method according to claim 9, characterized in that, In S2, the drying temperature is 80-100℃ and the drying time is 1-5h; In S3, the mixing temperature is 70–120℃ and the mixing time is 1–8 min; In S4, polyvinyl chloride resin, heat stabilizer, processing aid and at least part of lubricant are first added to a high-speed mixer for the first stage of mixing, and then fully vulcanized powdered nitrile rubber and carboxylated nitrile rubber-magnesium aluminum hydrotalcite predispersant are added and mixing continues.